PENGARUH KEMANDIRIAN, GAYA BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI SISWA KELAS X PROGRAM KEAHLIAN AKUNTANSI SMK PGRI 3 SIDOARJO - Saragih, Devi Kartika (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aimed to determine the effect of self-reliance, learning style and learning enviroment for accounting achievement in grade X of SMK PGRI 3 Sidoarjo for academic years 2013/2014. Sample was 107 students selected by using simple random sampling technique. Data were collected by questionnaires and documentation method. The method of analysis in this study was a correlation research with quantitative approach analysis, multiple linear regressions. According to analysys and results showed there is a significant effect between : self-reliance to the student learning results, there is a significant effect between students learning style to the student learning results, there is a significant effect between learning environment to the student learning results, and there is a simultaneous effect between self reliance learning style and learning environment to the learning results on X grade of accounting students in SMK PGRI 3 Sidoarjo no particial effect on self-reliance to achievement of accounting, there is no particial effect on learning style to achievement of accounting, there is no particial effect on learning enviromentto achievement of accounting, and there are no simultaneous effect on self-reliance, learning style and learning enviroment on the learning achievement of accounting